Development of amorphous silicon carbide semiconductor thin films for optoelectronic device applications - Yoon, Soon Fatt. (2008)
Its primary objective was to investigate the use of the electron cyclotron resonance chemical vapour deposition (ECR-CVD) technique to deposit amorphous and microcrystalline hydrogenated silicon carbide films (SiC:H) with a view for the eventual use of such films for optoelectronic applications.